2021
DOI: 10.1111/1365-2435.13869
|View full text |Cite
|
Sign up to set email alerts
|

Endothermy makes fishes faster but does not expand their thermal niche

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 65 publications
1
37
0
Order By: Relevance
“…This in turn, along with behavioral adaptations to maximize swim efficiency in a three dimensional environment [ 6 , 46 ], is argued to underpin the success of hunting strategies employed by larger white sharks [ 4 ]. Our estimate of cruising speed (0.6 m s -1 , 0.3 U TL s -1 ) is markedly lower than that recorded by both Carey et al (1982 [0.89 m s -1 , 0.51 TL s -1 ], shark size 457 cm TL, 943 kg) [ 33 ], more than half that of Semmens et al (2013) [2.25 m s -1 , 0.62 TL s -1 , shark sizes 280–450 cm TL, 195–839 kg] [ 29 ], and ~ 2/3 the mean swim speed reported by Watanabe et al (2019) [0.94 m s -1 , shark sizes 290–420 cm TL, 218–721 kg] In fact, our cruising speed estimates are more in line with those reported from biologging data by Harding et al, (2021) [ 7 ]. Our mean estimated fRMR was approximately half that reported by Semmens et al (723 mg O 2 kg −1 h −1 ) [ 29 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This in turn, along with behavioral adaptations to maximize swim efficiency in a three dimensional environment [ 6 , 46 ], is argued to underpin the success of hunting strategies employed by larger white sharks [ 4 ]. Our estimate of cruising speed (0.6 m s -1 , 0.3 U TL s -1 ) is markedly lower than that recorded by both Carey et al (1982 [0.89 m s -1 , 0.51 TL s -1 ], shark size 457 cm TL, 943 kg) [ 33 ], more than half that of Semmens et al (2013) [2.25 m s -1 , 0.62 TL s -1 , shark sizes 280–450 cm TL, 195–839 kg] [ 29 ], and ~ 2/3 the mean swim speed reported by Watanabe et al (2019) [0.94 m s -1 , shark sizes 290–420 cm TL, 218–721 kg] In fact, our cruising speed estimates are more in line with those reported from biologging data by Harding et al, (2021) [ 7 ]. Our mean estimated fRMR was approximately half that reported by Semmens et al (723 mg O 2 kg −1 h −1 ) [ 29 ].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies in adults and sub-adults of the species have suggested that white sharks have developed behavioral strategies that help offset the energetic costs of regional endothermy [ 6 ], including elevated average swim speeds (cruising speeds) [ 3 ] in comparison with species that do not exhibit regional endothermy, that provide a competitive advantage in resource exploitation. This hypothesis was supported by the results of a recent study that used a synthesis of bio-logging data from both ectotherm and endotherm fish, and concluded that the convergent evolution of endothermy in a range of fishes more likely driven by competitive advantages gained in ecological interactions and resource exploitation, rather than by thermal niche expansion [ 7 ]. Juvenile white sharks (JWS) exploit a very different habitat niche to their adult conspecifics [ 5 , 8 14 ], and rely on a mostly piscivorous based diet [ 15 – 19 ].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…They are an ectothermic species without the parallel arrangement of arteries and veins that function as counter-current heat exchangers in muscles (Carey and Gibson 1987). In general, ectothermic fishes are thought to have narrower thermal niches than regionally endothermic fishes with well-developed heat exchangers (e.g., tunas, lamnid sharks) (Block et al 1993;Weng et al 2005), although a recent study challenged this view (Harding et al 2021). Blue sharks represent an interesting example as they dive to great depths [occasionally > 1000 m, with the maximum record of 1706 m (Queiroz et al 2017)] and experience extensive water temperature ranges (up to 20 °C) (Stevens et al 2010;Campana et al 2011;Queiroz et al 2012) despite their ectothermic physiology.…”
Section: Introductionmentioning
confidence: 99%
“…During the prespawning period, capelin form relatively large and compact schools that are heavily preyed upon by humpback whales (Megaptera novaeangliae) as well as a number of other cetacean species including finback whales (Balaenoptera physalus), minke whales (Balaenoptera acutorostrata), whitebeaked dolphins (Lagenorhynchus albirostris), and short-beaked saddleback dolphins (Delphinus delphis) (Whitehead and Glass, 1985). The white shark's ability to maintain a warmer-thanambient body temperature likely enables expansion of its thermal niche and access to habitats largely limited to other top predators, accepting that regional endothermy is more associated with higher swim speeds rather than broader thermal niches (Harding et al, 2021). It is likely the white sharks are drawn to the abundant food supply of the SES during this period and at times may actively hunt or scavenge on cetaceans in the subzero waters just off the slope of the shelf, though we cannot rule out the possibility of white sharks foraging on the spawning capelin while on the shoal.…”
Section: Seasonality and Migrationmentioning
confidence: 99%